Noninvasive mechanical ventilation assistance in amyotrophic lateral sclerosis: a systematic review - Cunha-Correia, Carolina da; Gama, Mylana Dandara Pereira; Fontana, Pedro Nogueira; Fantini, Francisca Goreth Malheiro Moraes; Prado, Gilmar Fernandes; Dourado Júnior, Mário Emílio Teixeira; Schwingel, Paulo Adriano (São Paulo Medical Journal, 2025)
BACKGROUND: Respiratory failure is the most common cause of death in patients with amyotrophic lateral sclerosis (ALS), and morbidity is related to poor quality of life (QOL). Non-invasive ventilation (NIV) may be associated with prolonged survival and QOL in patients with ALS. OBJECTIVES: To assess whether NIV is effective and safe for patients with ALS in terms of survival and QOL, alerting the health system. DESIGN AND SETTING: Systematic review was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses reporting standards using population, intervention, comparison, and outcome strategies. METHODS: The Cochrane Library, CENTRAL, MEDLINE, LILACS, EMBASE, and CRD databases were searched based on the eligibility criteria for all types of studies on NIV use in patients with ALS published up to January 2022. Data were extracted from the included studies, and the findings were presented using a narrative synthesis. RESULTS: Of the 120 papers identified, only 14 were related to systematic reviews. After thorough reading, only one meta-analysis was considered eligible. In the second stage, 248 studies were included; however, only one systematic review was included. The results demonstrated that NIV provided relief from the symptoms of chronic hypoventilation, increased survival, and improved QOL compared to standard care. These results varied according to clinical phenotype. CONCLUSIONS: NIV in patients with ALS improves the outcome and can delay the indication for tracheostomy, reducing expenditure on hospitalization and occupancy of intensive care unit beds. SYSTEMATIC REVIEW REGISTRATION: PROSPERO database: CRD42021279910 — https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=279910.